Design and Implementation of AI-Driven Educational Resources in Higher Education: A Legal Perspective - S. V. Titova; K. V. Chikrizova (Высшее образование в России)
The purpose of this article is to answer the following research questions: 1) Is it legal to use educational materials created using AI in educational practice? 2) Is it possible to use educational materials developed using AI for commercial purposes? 3) Is it possible to protect the copyright to educational materials created using AI? The authors conduct a comparative literature analysis in the fields of education and law, as well as relevant legal frameworks and judicial practices in Russia and abroad. In the article authors also provides answers to three key questions mentioned above faced by modern educators when designing educational content. Is it possible to protect one’s copyright for educational content created using AI? In conclusion, the article presents some fundamental principles that should be followed when developing educational materials involving artificial intelligence technologies.